On-farm evaluation of integrated nutrient and pest management in Cicer arietinum L. - E, Leo Daniel Amalraj; G, Praveen Kumar; SK, Mir Hassan Ahmed; Desai, Suseelendra (Journal of Phytology, 2012)
Chickpea (Cicer arietinum L.) is the world’s third most important pulse crop. In chickpea, wilt caused by Fusarium oxysporum f. sp. ciceri is one of the major production constraints. On-farm demonstration on use of Trichoderma viride, PSB and Rhizobium was conducted during rabi (Nov-Jan) 2006 in Machanapally village, Ranga Reddy district, AP, India. At harvest, data on wilt incidence yield and related parameters were recorded. In T1, where seeds were treated with PSB+Rhizobium+T. viride followed by soil application of T. viride+PSB+Rhizobium after 30 DAS (mixed with 200 kg of FYM), wilt incidence was 4.5% and yield was 0.995 t.ha-1. In T2, where carbendazim was applied as seed treatment followed by the soil application of recommended doses of NPK, wilt incidence was 8.3% with a yield of 1.2 t.ha-1. In T3, where seeds were treated as in T1 and NPK was applied to soil as in T2, wilt incidence was 3.3% and crop yield was 1.13 t. ha-1. Highest plant dry mass (25.5 g.plant-1) and number of effective nodules (6.3 plant-1) were recorded in T3. To conclude, integrated nutrient and disease management is an ideal approach for chickpea cultivation.